Ossification of the Posterior Longitudinal Ligament: Etiology, Diagnosis, and Outcomes of Nonoperative and Operative Management. (March 2016) - Abiola, Rasheed; Rubery, Paul; Mesfin, Addisu
Study Design: Narrative review. Objective: To provide an overview on the diagnosis, natural history, and nonoperative and operative management of ossification of the posterior longitudinal ligament (OPLL). OPLL is a multifactorial condition caused by ectopic hyperostosis and calcification of the posterior longitudinal ligament. Familial inheritance and genetic factors have been implicated in the etiology of OPLL. The cervical spine is most commonly affected followed by the thoracic spine. The clinical manifestations range from asymptomatic to myelopathy or myeloradiculopathy. Methods: Using PubMed, studies published prior to October 2014 with the keywords "OPLL, etiology"; "OPLL, genetics"; "OPLL, spinal cord injury"; "OPLL, natural history"; "OPLL, non-surgical management"; OPLL, surgical management"; "OPLL, surgical complications" were evaluated. Results: The review addresses the etiology, epidemiology, classification, clinical presentation, imaging findings, and nonoperative and operative management of OPLL. Complications associated with surgical management of OPLL are also discussed. Conclusions: OPLL commonly presents with myelopathy and radiculopathy. Spine providers should consider OPLL in their differential diagnosis and when reviewing images. If surgical intervention is pursued, imaging-based measurements and findings can help in choosing an anterior versus posterior surgical approach.